Comparison of hand hygiene compliance self-assessment and microbiological hand contamination among healthcare workers in Mwanza region, Tanzania - Devis Rayson; Namanya Basinda; Ruanda Adam Pius; Jeremiah Seni (Elsevier, 2021)
Summary: Background: Compliance with hand hygiene (HH) practices remains a major challenge in preventing healthcare-associated infections (HCAI). Little is known whether self-reported HH compliance reflects the level of hand contamination microbiologically as a guide for specific infection prevention and control (IPC) measures. Methods: A cross-sectional study was conducted between July and September 2019 involving 18 healthcare facilities (HCF) in Mwanza region, Tanzania. It assessed HH using astructured questionnaire and microbiological analysis of hand samples for culture (n=212), and the WHO Hand Hygiene Self-Assessment Framework (2010) (n=74). Results: The overall median HH score (interquartile range) was 212.5 (190-245) and designated at basic level in the WHO framework. The scores progressively increased from basic level in health centres to intermediate level in a tertiary hospital. Self-reported HH compliance using the WHO recommended cut-off value of ≥81.0% was 10.8% (8/74). A total of 56 (26.4%) healthcare workers (HCWs) hands had bacterial contamination; 17.9% (n=38) by Gram negative bacteria (including coliforms, Acinetobacter spp and Pseudomonas aeruginosa), 8.0% (n=17) by meticillin-resistant Staphylococcus aureus (MRSA) and 0.5% (n=1) by both. Hand contamination was significantly higher in district hospitals (P-value=0.0437), and among HCWs residing in the rural areas (P-value=0.017). Conclusion: The median HH score amongst HCF in Mwanza region was at basic level. A quarter of HCWs hands were contaminated by bacteria which mismatched self-reported HH. A need to incorporate HH microbiological paramaters to the WHO HH assessment tool is needed, and future IPC interventional measures should be tailored to the HCF tier and in rural areas.